ANALISIS TUTURAN WAKIL GUBERNUR DKI JAKARTA SANDIAGA UNO - Ali Kusno (Balai Bahasa Kalimantan Barat, 2018)
Sandiaga Uno’s statements (Sandi) attract public attention because they are considered ridiculous. This research is to reveal the use of language or the meaning of the speech that often creates confusion and laughter by the people. This research is qualitative descriptive. The collection of data are using document analysis. The data source are the speech document that is published in the online media. This research is using the discourse analysis. Data analysis techniques is using interactive model. The results showed that the various uses and definition of the language of the speech is that he represents the new government of DKI Jakarta has not had a clear concept for development. The speeches that was delivered by Sandi to the public described the inability of DKI Jakarta’s government for dealing with various issues. As a public official should be able to be professional. If the problem has not got a solution, it should be not declared the statements that could be confusing and just shows the inability of the DKI Jakarta government.